1990
DOI: 10.3109/00365599009180859
|View full text |Cite
|
Sign up to set email alerts
|

Results of 5035 Stone Analyses: A Contribution to Epidemiology of Urinary Stone Disease

Abstract: Between 1978 and 1988 5,035 urinary calculi have been analysed by X-ray diffractometry. 1,615 of these stones have additionally been investigated by scanning electron microscopy (SEM). The overall sex-ratio was 1.86 (m/f). Ca-stones and uric acid containing stones are more frequent in male patients (m/f = 2.08 and 3.86, respectively) whereas infection stones and cystine stones show a higher rate of appearance in female patients (m/f = 0.6 and 0.88, respectively). The percentage of open surgery ranged about 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(40 citation statements)
references
References 8 publications
4
30
0
6
Order By: Relevance
“…19 During the ®rst year post injury, when immobilization hypercalciuria is a concern, an increased risk of kidney stones in men, Caucasians, and people between 40 and 60 years of age is consistent with ®ndings in the general population, 15,16,20 where calcium stones are predominant. 21 The dierential urinary excretion of calcium as a result of variation in hormones (such as testosterone) with age and gender has been hypothesized to account for the observed risk dierence in the general population. The potential in¯uence of these demographic factors on mineral metabolism during the acute phase of injury might explain the variation in stone risk, which needs further con®rmation.…”
Section: Discussionmentioning
confidence: 99%
“…19 During the ®rst year post injury, when immobilization hypercalciuria is a concern, an increased risk of kidney stones in men, Caucasians, and people between 40 and 60 years of age is consistent with ®ndings in the general population, 15,16,20 where calcium stones are predominant. 21 The dierential urinary excretion of calcium as a result of variation in hormones (such as testosterone) with age and gender has been hypothesized to account for the observed risk dierence in the general population. The potential in¯uence of these demographic factors on mineral metabolism during the acute phase of injury might explain the variation in stone risk, which needs further con®rmation.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors related to the onset of UC; however, no precise etiology has been confirmed yet (Siener, 2006). Various domestic and international studies have confirmed that the etiology of UC is closely related to environmental factors (Finlayson, 1974;Embon et al, 1990;Leusmann et al, 1990), as well as to genetic factors, ethnicity, gender, age, dietary habits, urinary biochemical abnormalities, etc. (Siener, 2006;Park et al, 2010;Kirejczyk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of stone disease depends on various environmental factors (climatic changes, geographical locations, dietary habits, and obesity) and as well as genetic factors (sex, age, race, idiopathic hypercalciuria, hyperoxaluria, and hyperuricosuria) (4) According to the literature, about 25% of patients with urolithiasis have a family history of stone disease and the relative risk of stone formation is higher in men with a family history than in women those without a family history. (5, 6) Family history positivity has been subjected to a number of studies in recent years (11,12) The aim of this study is to examine the influence of family history and to find the recurrence rate on urinary stone disease in Sri Lanka.…”
Section: Introductionmentioning
confidence: 99%